PRESERVATION OF PHYSICAL AND MENTAL HEALTH OF JUNIOR SCHOOL STUDENTS IN TIME FORMATION OF PERSISTENCE BY MEANS MOVING GAMES - Z.M. Dikhtyarenko (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the protection o f physical and psychologic health of young pupils by means of mobile games